2016
DOI: 10.1016/j.ijpara.2015.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles secreted by Schistosoma mansoni contain protein vaccine candidates

Abstract: Herein we show for the first time that Schistosoma mansoni adult worms secrete exosome-like extracellular vesicles ranging from 50 to 130nm in size. Extracellular vesicles were collected from the excretory/secretory products of cultured adult flukes and purified by Optiprep density gradient, resulting in highly pure extracellular vesicle preparations as confirmed by transmission electron microscopy and Nanosight tracking analysis. Extracellular vesicle proteomic analysis showed numerous known vaccine candidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
165
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(176 citation statements)
references
References 25 publications
11
165
0
Order By: Relevance
“…Their role is still unknown, although they have been suggested to play roles in fundamental biological processes such as larval penetration [69] and modulation of the immune response [70,71], in the transition from the free-living to the parasitic stage [72], and have even been explored as vaccine candidates against hookworm infections [73]. It is interesting to note that EVs from other helminths are enriched for many known vaccine candidate antigens [21]. Since SCP/TAPS proteins are abundant in the EVs secreted by T. muris , their potential use as vaccines should be further explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their role is still unknown, although they have been suggested to play roles in fundamental biological processes such as larval penetration [69] and modulation of the immune response [70,71], in the transition from the free-living to the parasitic stage [72], and have even been explored as vaccine candidates against hookworm infections [73]. It is interesting to note that EVs from other helminths are enriched for many known vaccine candidate antigens [21]. Since SCP/TAPS proteins are abundant in the EVs secreted by T. muris , their potential use as vaccines should be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…For the isolation of EVs, the media obtained after differential centrifugation were processed as described previously [21]. Briefly, ES products were concentrated using a 10 kDa spin concentrator, followed by centrifugation for 45 min at 12,000  g to remove larger vesicles.…”
Section: Methodsmentioning
confidence: 99%
“…Significantly, the infective stage was found to be much more prolific exosome producers than the adult worm stage, possibly reflecting the demands of transition from vector to host at this point in the life cycle. Sotillo et al further reported that adult S. mansoni worms release 50–130nm-sized exosome vesicles, containing over 80 identifiable proteins 5 of which are tetraspanins and an abundant saposin-like protein [54]. These authors also highlighted that a number of known Schistosome vaccine candidate antigens, including the tetraspanins discussed above, are prominent components of the exosomes.…”
Section: Protein-mediated Interactionsmentioning
confidence: 95%
“…EVs are small membrane-bound vesicles that are generally classified into two major types, exosomes and microvesicles, based on their size, biogenesis, and composition. The secretion of EVs was demonstrated in several parasites such as the protozoa Plasmodium falciparum [27] and Trypanosoma brucei [28], and helminths [29] including schistosomes [30][31][32]. The secretion of EVs was demonstrated in several parasites such as the protozoa Plasmodium falciparum [27] and Trypanosoma brucei [28], and helminths [29] including schistosomes [30][31][32].…”
Section: Introductionmentioning
confidence: 99%